Bocaparvovirus, Erythroparvovirus and Tetraparvovirus in New World Primates from Central America - Chaves Ramírez, Andrea (2020)
Parvoviruses in the genera Bocaparvovirus (HBoV), Erythroparvovirus (B19) and Tetraparvovirus (PARV4) are the only autonomous parvoviruses known to be associated with human and non‐human primates based on studies and clinical cases in humans worldwide and non‐human primates in Asia and Africa. Here, the presence of these agents with pathogenic potential was assessed by PCR in blood and faeces from 55 howler monkeys, 112 white‐face monkeys, 3 squirrel monkeys and 127 spider monkeys in Costa Rica and El Salvador. Overall, 3.7% (11/297) of the monkeys had HboV DNA, 0.67% (2/297) had B19 DNA, and 14.1% (42/297) had PARV4 DNA, representing the first detection of these viruses in New World Primates (NWP). Sex was significantly associated with the presence of HBoV, males having greater risk up to nine times compared with females. Captivity was associated with increased prevalence for PARV4 and when all viruses were analysed together. This study provides compelling molecular evidence of parvoviruses in NWPs and underscores the importance of future research aimed at understanding how these viruses behave in natural environments of the Neotropics and what variables may favour their presence and transmission.